The precipice neoliberalism, the pandemic and the urgent need for radical change - Chomsky, Noam 1928- (Haymarket Books, 2021)
A collection of interviews with the world's leading public intellectual from the time of the rise of Donald Trump to power to the end of his presidency. In The Precipice, Noam Chomsky sheds light into the phenomenon of Trumpism, exposes the catastrophic nature and impact of Trump's policies on people, the environment, and the planet as a whole, and captures the dynamics of the brutal class warfare launched by the masters of capital to maintain and even enhance the features of a dog-eat-dog society to the unprecedented mobilization of millions of people against neoliberal capitalism, racism, and police violence"--
Description based on publisher supplied metadata and other sources
Keywords: Trump, Donald -- 1946-; Chomsky, Noam -- 1928-; Neoliberalism -- United States; Social change; Neoliberalismus; Klassenkampf; Interview